Analysis of Potential, Impact and Design of a Sustainable Ecotourism Management System Using an Industrial Engineering Approach in The Kuala Bubon Mangrove Forest, West Aceh - Rizky Aprinas Gading; Muhammad Asiraf; Reval Legar Seprijar; Jastri Nurul Hayani; Ulhaq, Riza (LPPM Politeknik Aceh Selatan, 2024)
The discourse of the West Aceh government and the Ministry of Tourism and Creative Economy, which aims to develop the Kuala Bubon West Aceh mangrove forest area into an ecotourism site to boost the community's economy, has drawn attention from many parties. This is due to the rich biodiversity present in the mangrove forest. Pre-ecotourism studies need to be conducted to ensure that the use of this forest can be managed properly, including studying potential tourist attractions, analyzing negative impacts, and engineering a sustainable ecotourism management industry. This involves using an industrial engineering approach, which offers an optimal framework for achieving these goals. The research was conducted in the Kuala Bubon mangrove forest, West Aceh, in July 2024. Survey techniques and direct observation were used to gather data on the ecotourism potential in the Kuala Bubon mangrove forest. This potential data will be mapped using Quantum GIS and then analyzed to assess the potential and impact of environmental damage as part of ecotourism and the ecosystem. The impact of the damage will then be addressed with alternative industrial engineering solutions, creating an effective management design using AutoCAD. The research results identified five ecotourism attraction points: sunset observation ecotourism, flora & fauna exploration, fishing, duck games, and shellfish searching. Based on this potential, a negative impact analysis and industrial engineering of the ecotourism area will be conducted, focusing on three aspects: infrastructure, waste management, and the utilization of renewable energy.Type your abstract here.